PENGARUH KEPEMIMPINAN, BUDAYA ORGANISASI, LINGKUNGAN KERJA DAN KOMITMEN TERHADAP KINERJA PENGELOLA PENGADAAN BARANG/JASA MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING DI KEMENTERIAN KESEHATAN - Sufyati H.S; Leberina Alfonsina Dodop (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
This study aims to analyze the influence of leadership, organizational culture, workenvironment, and competence on the performance of managers of procurement ofgoods/services with job satisfaction as an intervening variable in the Ministry of Health. Thedata used in this study is primary data obtained from distributing questionnaires to 145employees managing the procurement of goods/services of the Ministry of Health asrespondents. The sampling technique used is simple random sampling. Structural EquationModeling (SEM) with AMOS was used to test the research hypothesis. The results of thedirect influence analysis showed that leadership, work environment and competence had apositive and significant effect on job satisfaction, while organizational culture had anegative and insignificant effect on job satisfaction. Leadership, organizational culture andwork environment have a positive and insignificant effect on performance, while competenceand job satisfaction have a positive and significant effect on performance. The results of theindirect influence analysis show that leadership, organizational culture, work environmentand competence have a positive and significant effect on performance through jobsatisfaction.